2023
DOI: 10.1021/acsomega.2c07484
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Radiolabeling, and In Vitro and In Vivo Characterization of Heterobivalent Peptidic Agents for Bispecific EGFR and Integrin αvβ3 Targeting

Abstract: Radiolabeled heterobivalent peptidic ligands (HBPLs) are a highly promising compound class for the sensitive and specific visualization of tumors as they often exhibit superior properties compared to their monospecific counterparts and are able to concomitantly or complementarily address different receptor types. The combination of two receptor-specific agents targeting the epidermal growth factor receptor (EGFR) and the integrin α v β 3 in one HBPL would constitute a synergistic combination of binding motifs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…This assumption is supported by a very recent study where we developed an EGFR- and integrin α v β 3 -bispecific radioligand that showed no EGFR-associated A431 tumor cell uptake and affinity but only integrin-mediated U87MG tumor cell interaction in in vitro studies. A subsequent in vivo PET/CT imaging and ex vivo biodistribution study in A431 tumor-bearing xenograft mice—having been conducted to identify a potential EGFR-specific tumor uptake occurring despite the discouraging in vitro results—confirmed the absent EGFR-specificity of the developed agent not only in vitro, but also in vivo [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…This assumption is supported by a very recent study where we developed an EGFR- and integrin α v β 3 -bispecific radioligand that showed no EGFR-associated A431 tumor cell uptake and affinity but only integrin-mediated U87MG tumor cell interaction in in vitro studies. A subsequent in vivo PET/CT imaging and ex vivo biodistribution study in A431 tumor-bearing xenograft mice—having been conducted to identify a potential EGFR-specific tumor uptake occurring despite the discouraging in vitro results—confirmed the absent EGFR-specificity of the developed agent not only in vitro, but also in vivo [ 54 ].…”
Section: Resultsmentioning
confidence: 99%